Perception of service quality, satisfaction, and behavioral intentions in Ayurveda healthcare - P. Suhail; Y. Srinivasulu (Journal of Ayurveda and Integrative Medicine, 2021)
Background: Based on the previous literature it is confirmed that Performance-based service quality and patient satisfaction are major antecedents of behavioral intentions in the healthcare sector. Here, the study deals with the same variables under the framework of Ayurveda healthcare. Objectives: The study is an attempt to understand the perceptional differences of healthcare consumers in Ayurveda, by analyzing the relationship between the service quality, satisfaction, and behavioral intentions in Ayurveda. Materials and methods: Using the convenient sampling technique, 404 samples were collected through direct interview, with a structured questionnaire from the in-patients of 20 accredited Ayurveda hospitals from the northern part of Kerala, a southern state of India. Respondents of the study consist of mostly women who were aged above 40. ANOVA and t-test were used to evaluate the differences in the perception of healthcare consumers, and multiple regression analysis and structural equation modeling were applied to propose two relationship models from the study. Results: The perception of healthcare consumers are found to vary for service quality and patient satisfaction according to socio-economic variables except for the education factor. Later the test on the impact of performance-based service quality on patient satisfaction and the mediation model showed a significant influence between the variables. Conclusion: The results of the study could empirically prove the relationships of these variables significantly and it can assure some quality contributions to the healthcare managers to modify their business policies in the future.